EFFECT OF INCENTIVE SYSTEM MANAGEMENT ON EMPLOYEE PERFORMANCE OF SELECTED DEPOSIT MONEY BANKS IN CROSS RIVER STATE, NIGERIA - Margaret, Agbor Oka (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study examine the effect of incentive system management on employee performance of selected deposit money banks in Cross River State, Nigeria. The study used structured questionnaires from the six selected deposit money banks in the study area. The researcher used multiple regression analysis to analyze the data obtained from the selected banks. The result of the study shows that the first variables of the study, pay-rise has a positive and significant effects on employee performance and the effect is statistically significant (p0.05). Bonus has a negative but insignificant effect on employee performance in the study area. Recognition has a positive effects on employee performance and the effect is statistically significant (p0.05) and in line with a priori expectation. The researcher concluded that incentive appeal to employees in a completely different manner. Thus, the use of appropriate incentive system is key to achieving organizational outcomes. The researcher recommends that the use of a combination of more than one reward system such as recognition and pay-rise is needed to improve employee performance in the study area.